Resemblance and symmetries of geometric patterns - Alt, Helmut; Blömer, Johannes (Data structures and efficient algorithms)

Improvement of PV-Performance by Partly Structured Surfaces - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 6th Photovoltaic Science and Engineering Conference, New Delhi (Indien), 10.–14. Februar 1992, Vol 1, S. 1110.)

Hinweise zur Modellbildung und Simulation des Strahlungseinfalls in PV-Module - Krauter, Stefan (Solar Energy Simulation Workshop der DGS, Oldenburg (Deutschland))

Reflexionsverringerung an PV-Modulen durch partiell strukturierte Deckgläser. - Krauter, Stefan; Hanitsch, Rolf (Tagungsband des Achten Internationalen Sonnenforums, Berlin (Deutschland), 30. Juni – 3. Juli 1992, S. 736–741)

Measuring the Heat–Transfer Coefficient of PV-Modules - Krauter, Stefan; Hanitsch, Rolf; Diwisch, R.; Diwisch, N.

Performance of a Partly Structured Surface at a PV-Module - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 11th European Photovoltaic Solar Energy Conference and Exhibition, Montreux (Schweiz), 12.–16. Oktober 1992, S. 1351–1354)

Mechanisms of Symmetry Creation - Dellnitz, Michael; Golubitsky, Martin; Melbourne, Ian (Bifurcation and Symmetry)

Generic Bifurcations of Pendula - Dellnitz, Michael; Marsden, Jerrold E.; Melbourne, Ian; Scheurle, Jürgen (Bifurcation and Symmetry)

Generic bifurcation of Hamiltonian vector fields with symmetry - Dellnitz, M; Melbourne, I; Marsden, J E (Nonlinearity)

High performance universal hashing, with applications to shared memory simulations - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Data structures and efficient algorithms)

Hashing strategies for simulating shared memory on distributed memory machines - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the performance of networks with multiple busses - Meyer auf der Heide, Friedhelm; Pham, Hieu Thien (STACS 92)

Dynamic Hashing in Real Time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (TEUBNER-TEXTE zur Informatik)

The Philips Research System for Continuous-Speech Recognition: Overview and Evaluation on the DRAPA RM Task - Aubert, Xavier L.; Ney, Hermann; Haeb-Umbach, Reinhold (DRAPA Speech Workshop)

Improvements in Speech Recognition for Voice Dialling in the Car Environment - Geller, Dieter; Haeb-Umbach, Reinhold; Ney, Hermann (ESCA Workshop on Speech Recognition in Adverse Conditions, Cannes-Mandelieu)

A modified trellis coding technique for partial response channels - Haeb-Umbach, Reinhold (IEEE Transactions on Communications)
The problem of trellis coding for multilevel baseband transmission over partial response channels with transfer polynomials of the form (1+or-D/sup N/) is addressed. The novel method presented here accounts for the channel memory by using multidimensional signal sets and partitioning the signal set present at the noiseless channel output. It is shown that this coding technique can be viewed as a generalization of a well-known procedure for binary signaling: the concatenation of convolutional codes and inner block codes that are tuned to the channel polynomial. It results in high coding gains with moderate complexity if some bandwidth expansion is accepted.

Trellis codes for partial-response magnetooptical direct overwrite recording - Haeb-Umbach, Reinhold; Lynch, Robert (IEEE Journal on Selected Areas in Communications)
The authors present conditions on the error sequences between channel input sequences which guarantee certain lower bounds on the free Euclidian distance at the output of a partial-response (PR) class I or II channel. From these expressions, trellis codes are derived which improve performance of binary signaling over noisy PR channels with reduced complexity maximum-likelihood sequence detection. They are shown to be compatible with the input restriction caused by the magnetooptical resonant coil direct overwrite recording scheme. The codes achieve high signal-to-noise ratio coding gains of 3 dB (on PR class I) and 2.2 dB (on PR class II) with rates as close to, but strictly less than, the capacity of the initial input restriction as desired. The performance of these codes is analyzed with an optical channel simulation system which shows that one code has the rare but highly desirable property that its maximum-likelihood sequence detector (MLSD) is less complex than the MLSD of the reference system and still achieves an error rate performance gain of 1.8 dB

Linear Discriminant Analysis for Improved Large Vocabulary Continuous Speech Recognition - Haeb-Umbach, Reinhold; Ney, Hermann (ICASSP, San Francisco)
The interaction of linear discriminant analysis (LDA) and a modeling approach using continuous Laplacian mixture density HMM is studied experimentally. The largest improvements in speech recognition could be obtained when the classes for the LDA transform were defined to be sub-phone units. On a 12000 word German recognition task with small overlap between training and test vocabulary a reduction in error rate by one-fifth was achieved compared to the case without LDA. On the development set of the DARPA RM1 task the error rate was reduced by one-third. For the DARPA speaker-dependent no-grammar case, the error rate averaged over 12 speakers was 9.9%. This was achieved with a recognizer using LDA and a set of only 47 Viterbi-trained context-independent phonemes.

Improvements in Beam Search for 10,000-Word-Continuous Speech Recognition - Ney, Hermann; Haeb-Umbach, Reinhold; Tran, B. H.; Oerder, Martin (ICASSP, San Francisco)
This paper describes the improvements in a time synchronous beam search strategy for a 10000-word continuous speech recognition task. The improvements are based on two measures: a tree-organization of the pronunciation lexicon and a novel look-ahead technique at the phoneme level, both of which interact directly with the detailed search at the state levels of the phoneme models. Experimental tests were performed for four speakers on a 12306-word task. As a result of the above measures, the overall search effort was reduced by a factor of 17 without a loss in recognition accuracy.

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard